FLOW UNITS DETERMINATION USING FLOW ZONE INDICATOR FOR CARBONATE RESERVOIR - Abdul Haris; Agus Riyanto; Tri Aji Adi Harsanto; Ambar Rachmanto; Adang Sukmatiawa (Program Studi Fisika Universitas Negeri Jakarta, 2018)
In the last few years, the use of flow unit technique in the oil and gas industry has shown a great deal of success. Porosity and permeability from wire-line log and special core data analysis (SCAL) along with its cementation exponent value were integrated to characterize the reservoir in terms of pore volume caused by facies changing. In this work, we determine flow unit of the carbonate reservoir, which is applied to the Northwest Java Basin Field, Indonesia by performing the flow unit analysis, which allows approximating absolute permeability. Furthermore, the quantity and the flow unit of the reservoir rock is also determined to identify the secondary porosity. To reduce the level of uncertainty, wire-line logs data were validated with core data before it is used to interpret the reservoir. Subsequently, the result can be extrapolated to un-cored wells. Our experiment shows that flow units can be determined reliably from the integration between porosity and permeability, which have defined two different rock types in term of flow unit zone. The correlation of the flow units between wells leads to the definition of reservoir quality.